Present-Biased Envy, Inequality, and Growth - Kirill Borissov; Mikhail Pakhnin; Ronald Wendner (CESifo GmbH, 2024)
We take into account that envy (relative consumption concerns) is more pronounced in the present than in the future. We consider a Ramsey-type model in which agents differ only in their initial capital endowments but are identical in their exogenous parameters. Agents' preferences exhibit present-biased envy: agents are naive and care about how their consumption levels compare to that of others in the current period. Our results suggest that present-biased envy affects both the level of inequality and the income level in an economy. First, present-biased envy generates the Matthew effect (the relatively rich get richer while the relatively poor get poorer), leading to a highly unequal long-run distribution of wealth. After some finite time, only those agents who were the wealthiest from the outset own the entire capital stock. All other agents are in the maximum borrowing state and spend their wages to repay the debt. Second, present-biased envy makes agents effectively more impatient, lowering the long-run capital stock and the aggregate income level compared to those in an economy without envy.
Keywords: D15; D31; D50; D91; O40; 330; relative consumption; envy; time inconsistency; sliding equilibrium; perfect foresight; wealth distribution